2021
DOI: 10.1039/d1fo00953b
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of chitooligosaccharides on acetaminophen-induced liver injury

Abstract: Currently, drug-induced liver injury caused by acetaminophen (APAP) is the second leading cause of human liver transplantation. The only clinical antidote treatment for APAP-induced liver injury is N-acetyl-L-cysteine (NAC), which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Several intervention studies confirmed that TNF expression alters the severity of AILI [ 89 , 166 , 191 , 226 , 227 ]. Combination therapy of boldine and NAC significantly reduces the expression of inflammatory markers, including TNF-α, IL-1β, and IL-6 [ 228 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 98%
See 1 more Smart Citation
“…Several intervention studies confirmed that TNF expression alters the severity of AILI [ 89 , 166 , 191 , 226 , 227 ]. Combination therapy of boldine and NAC significantly reduces the expression of inflammatory markers, including TNF-α, IL-1β, and IL-6 [ 228 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 98%
“…Plentiful clinical and experimental animal data indicate that IL-6 is highly induced in AILI and inhibiting IL-6 expression by multiple interventions can significantly alleviate the liver injury caused by APAP. All these studies suggest that IL-6 plays a considerable role in promoting the inflammatory response process in AILI [ 72 , 175 , 177 , 191 , 192 ]. However, a few contrary reports suggest that IL-6 deficient mice lacking the expression of cytoprotective heat shock proteins (HSPs) would be more susceptible to APAP hepatotoxicity [ 193 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%
“…[7] Inhibiting or deleting CYP2E1 has been shown to effectively reduce the production of NAPQI, block ROS production, and alleviate inflammation in APAP-induced mouse models. [11][12][13] Therefore, this approach has the potential to be a useful therapy in treating APAP-induced ALF. 18𝛽-Glycyrrhetinic acid (18𝛽-GA), a in vivo metabolic component of glycyrrhiza acid while is commonly used as a liver protection drug in clinic, is reported to be a potent inhibitor of CYP2E1, [14] indicating that 18𝛽-GA could be a candidate for ALF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐acetyl‐L‐cysteine (NAC), a precursor of GSH, is currently the only drug employed for the clinical detoxification of APAP‐induced hepatotoxicity 12,13 . However, its application is limited owing to its narrow therapeutic window and numerous serious side effects 14,15 . Therefore, developing more effective treatment strategies with fewer side effects is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, its application is limited owing to its narrow therapeutic window and numerous serious side effects. 14,15 Therefore, developing more effective treatment strategies with fewer side effects is urgently required.…”
mentioning
confidence: 99%